EXPLORING STUDENTS' ACCEPTANCE OF DIGITALIZATION IN VOCATIONAL SCHOOL ENGLISH LEARNING - Rendra Aji Putra; Wiyaka; Dias Andri Susanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT The rapid development of digital technology has transformed English language learning by providing various opportunities for students to access learning resources, interact with digital platforms, and develop language skills. However, successful digital integration depends not only on technological availability but also on students’ acceptance and willingness to use digital technologies. This study aimed to investigate vocational high school students’ acceptance of digitalization in English language learning based on the Technology Acceptance Model (TAM), focusing on Perceived Usefulness (PU) and Perceived Ease of Use (PEOU). This study employed an explanatory sequential mixed-methods design. Quantitative data were collected through a close-ended questionnaire administered to nineteen vocational high school students, while qualitative data were obtained through open-ended questionnaires and semi-structured interviews with selected participants. The data were analyzed using descriptive statistics and thematic analysis based on the TAM framework. The findings revealed that students demonstrated a high level of acceptance toward digitalization in English learning. The results showed that Perceived Usefulness obtained an overall mean score of 3.86, indicating that students considered digital technologies beneficial for improving English skills, accessing learning materials, increasing engagement, and supporting task completion. Meanwhile, Perceived Ease of Use achieved an overall mean score of 3.70, suggesting that students perceived digital technologies as easy to operate despite several technical challenges. The study concludes that students’ acceptance of digitalization is strongly influenced by their perceptions of usefulness and ease of use. The findings provide practical implications for English teachers and schools in designing accessible and effective digital learning environments. Keywords: digitalization; English language learning; Technology Acceptance Model; perceived usefulness; perceived ease of use; vocational high school students